2011
DOI: 10.1074/jbc.m110.178483
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Hematopoietic Differentiation of Mouse Embryonic Stem Cells using Soluble Heparin and Heparan Sulfate Saccharides

Abstract: Heparan sulfate proteoglycans (HSPG) encompass some of the most abundant macromolecules on the surface of almost every cell type. Heparan sulfate (HS) chains provide a key interaction surface for the binding of numerous proteins such as growth factors and morphogens, helping to define the ability of a cell to respond selectively to environmental cues. The specificity of HSprotein interactions are governed predominantly by the order and positioning of sulfate groups, with distinct cell types expressing unique s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 40 publications
3
68
0
Order By: Relevance
“…The loss of endogenous HS is not deleterious to self-renewal and pluripotency. However, HS is critical when cells are challenged to differentiate by at least three distinct protocols, in vitro neural differentiation, embryoid-body mediated hematopoiesis, and leukemia inhibitory factor (LIF) withdrawal [25,34,38]. One of the hallmarks of early differentiation is the response to autocrine signals, many of which are dependent on HS, for example, the FGF-mediated system described in this study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The loss of endogenous HS is not deleterious to self-renewal and pluripotency. However, HS is critical when cells are challenged to differentiate by at least three distinct protocols, in vitro neural differentiation, embryoid-body mediated hematopoiesis, and leukemia inhibitory factor (LIF) withdrawal [25,34,38]. One of the hallmarks of early differentiation is the response to autocrine signals, many of which are dependent on HS, for example, the FGF-mediated system described in this study.…”
Section: Discussionmentioning
confidence: 94%
“…The phenotypes of these cells, primarily their ability to maintain self-renewal, differ significantly [35,38]. Both the knockout Ext1 À/À ES cell lines (described previously [25,34] and here), the stably transfected RNAi line (this study) and the Ext1 flox/flox ES cell line [38], can self-renew and maintain pluripotency in contrast to previous reports of Ext1 kd cells generated by transient RNA interference [35]. The loss of endogenous HS is not deleterious to self-renewal and pluripotency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in EXT1 or EXT2-deficient mice, On the other hand, other groups reported that EXT1-deficient ES cells, which have no HS chains, could not differentiate (36,(40)(41)(42). In the EXT1-deficient ES cells, inhibition of Nanog expression via FGF4 signaling was eliminated because FGF4 signaling, the differentiation trigger, could not work with deficient HS chains.…”
Section: The Function Of the Hs Chain In Mouse Es Cellsmentioning
confidence: 90%
“…In contrast, a total lack of Ext1 prevents both spontaneous differentiation as well as directed neural differentiation (Johnson et al 2007;Kraushaar et al 2010;Holley et al 2011). A recent study by Holley and coworkers (2011) showed that Ext1 -/-cells do form embryonic bodies (EBs), an in vitro three-dimensional (3D) model for ES cell differentiation, with a subsequent increase in early mesodermal markers.…”
Section: Studies Using Ext1mentioning
confidence: 99%